Stress management coping strategies among academic leaders in an institution of higher learning / Nor Sa'adah Aziz - Aziz, Nor Sa'adah (2014)
Academic leaders in institutions of higher learning (IHL) perform multiple tasks where they have to handle political and bureaucratic accountability whilst trying to balance educational, managerial, and leadership to promote their institutions. Coping with such challenging responsibilities can be stressful and hence they need to equip themselves with stress management coping strategies. Therefore, this study was conducted with the aim to identify stress management coping strategies used by academic leaders in an institution of higher learning (IHL) located in Selangor. The study involved a total of 46 academic leaders from 3 branch campuses in one IHL. The study employed a mixed-methods research design where data were collected using a questionnaire and semi-structured interviews. The quantitative data were statistically analyzed using SPSS version 20 while the qualitative data were analyzed using thematic analysis to trace emerging themes. The findings revealed that academic leaders experienced a high level of stress when handling bureaucratic aspects of their roles and responsibilities followed by the demand and status of leadership, and the management of others. They faced least amount of stress with regards to role confusion. Besides that, findings showed that a majority of academic leaders opted towards problem focused engagement strategies such as cognitive restructuring and problem solving strategies followed by emotion-focused engagement which included expressing emotion and social support strategies. Findings also indicated that there were no significant differences in coping strategies used by male and female academic leaders. Nevertheless, there was a significant difference in the mean score for problem solving, express emotions, social support and social withdrawal coping strategies between novice and experienced academic leaders. The findings of this study imply that academic leaders in this study are rather engaged and well informed of stress coping strategies but could be better informed if top management would take steps to better understand the complexities of the roles of academic leaders and provide the necessary support in helping them to manage stress.